Planning in Middle Childhood: Early Predictors and Later Outcomes. Issue 4 (29th January 2014) - Friedman, Sarah L.; Scholnick, Ellin K.; Bender, Randall H.; Vandergrift, Nathan; Spieker, Susan; Hirsh Pasek, Kathy; Keating, Daniel P.; Park, Yoonjung; The NICHD Early Child Care Research Network
<x xml:space="preserve">Abstract</x> Data from 1, 364 children and families who participated in the National Institute of Child Health and Human Development's Study of Early Child Care and Youth Development were analyzed to track the early correlates and later academic outcomes of planning during middle childhood. Maternal education, through its effect on parenting quality when children were 54 months old, predicts their concurrent performance on sustained attention, inhibition, and short‐term verbal memory tests. This performance predicts planning in first grade, which predicts third‐grade reading and mathematics attainment, but not the rate of growth in academic skills from first to fifth grades. This path was also found when the same parenting, cognitive, and academic constructs were measured at later time points.